Identification of rare missense mutations in NOTCH2 and HERC2 associated with familial central precocious puberty via whole-exome sequencing. (2nd August 2020) - Lee, Hae Sang; Jeong, Hwal Rim; Rho, Jung Gi; Kum, Chang Dae; Kim, Kyung Hee; Kim, Do Wan; Cheong, Jae Youn; Jeong, Seon-Yong; Hwang, Jin Soon
Abstract: Objective: Genetic factors play a critical role in pubertal progression; however, mutations associated with central precocious puberty (CPP) have been reported only in four genes: KISS1, KISS1R, DLK1, and MKRN3 . This study aimed to identify novel, potentially pathogenic variants in patients with familial CPP via whole-exome sequencing (WES). Methods: WES analysis was applied in 28 patients (25 girls and three boys) belonging to 14 families, wherein all siblings were diagnosed with CPP. Data analysis aimed to select only very rare variants (minor allele frequency <1%). Nonsense, splice-site, and frameshift variants were considered the most ideal candidate variants. Additionally, non-synonymous missense variants predicted as being deleterious using in silico analysis tools were further considered. Results: The analysis of exome sequencing data resulted in the identification of rare mutations in two promising candidate genes ( NOTCH2 and HERC2 ) in a family. Siblings with CPP exhibited two heterozygous missense mutations (p. Leu15Phe in NOTCH2 and p. Arg4081His in HERC2 ). Moreover, their parents without history of CPP had a missense variant in either NOTCH2 or HERC2 . Conclusions: We identified new candidate genes with potential roles in pubertal development. Digenic inheritance of the two genetic mutations associated with the Notch signaling pathway may have a synergistic effect resulting in CPP.